Innovative Solutions for AI Contribution in Developing Socially Inclusive Education for Children - Loso Judijanto; Asfahani Asfahani; Nova Krisnawati; Ayi Abdurahman; Anjana Prusty (Edujavare Publishing, 2022)
This study explores the innovative solutions offered by artificial intelligence (AI) in advancing social inclusion within educational environments for children. Through a qualitative research approach involving interviews, focus groups, observational studies, and document analysis, the research investigates the potential of AI-driven interventions to address barriers to social inclusion and promote equity in education. The findings highlight stakeholders' recognition of AI's transformative potential, students' emphasis on inclusive design principles, and concerns regarding privacy and bias. Moreover, positive outcomes observed in classrooms, such as improved efficiency in personalized instruction and increased student engagement, underscore the promise of AI in fostering more equitable learning environments. However, challenges such as the digital divide and algorithmic bias necessitate further research and the development of ethical guidelines to ensure responsible deployment of AI technologies. Overall, this research contributes to understanding the role of AI in advancing children's social inclusive education and provides recommendations for future research and policy development in this critical area.